Targeting FGFR pathway in breast cancer. (February 2018) - Perez-Garcia, J.; Muñoz-Couselo, E.; Soberino, J.; Racca, F.; Cortes, J.
Abstract: Developments in breast cancer biology over the last years have permitted deconstructing the molecular profile of the most relevant breast cancer subtypes. This has led to an increase in therapeutic options, including more effective personalized therapy for breast cancer and substantial improvements in patient outcomes. Although currently there are only a few targeted therapies approved for metastatic breast cancer, the discovery of druggable kinase gene alterations has radically changed cancer treatment by providing novel and successfully actionable drug targets. Fibroblast growth factors and their receptors (FGFRs) participate in different physiologic processes and also play an essential role in cancer cell proliferation, survival, differentiation, migration, and apoptosis. This article summarizes the main molecular alterations of FGFRs, as well as the available preclinical and clinical data with FGFR inhibitors in breast cancer, and discusses new opportunities for the clinical development of these agents in patients with breast cancer.